Early toxicity of hypofractionated radiotherapy for prostate cancer - Krupa, Pavel; Ticha, Hana; Kazda, Tomas; Dymackova, Radana; Zitterbartova, Jana; Odlozilikova, Anna; Kominek, Libor; Bobek, Lukas; Kudlacek, Ales; Slampa, Pavel (Biomedical papers, 2016)
Background: Hypofractionated accelerated radiotherapy (HART) is now a feasible option for prostate cancer treatment apropos toxicity, biochemical control and shortening of treatment. The aim of this study was to investigate hypofractionated schedules in the treatment of patients with localized prostate cancer.Patients and Methods: Between 2011-2014, 158 patients were treated using the RapidArc technique with IGRT. The target volume for low risk patients was the prostate alone with a prescribed dose of 20x3.0 Gy (EQD2=77 Gy). Targets volumes for intermediate and high risk patients were prostate and two thirds of the seminal vesicles with a prescribed dose 21-22x3.0/2.1 Gy (EQD2=81/45.4-84.9/47.5). Based on radiobiological modelling of early toxicity, we used four fractions per week in the low risk group and four fractions in odd weeks and three fractions in even weeks in intermediate and high risk groups. The RTOG/EORTC toxicity scale was used.Results: Early genitourinary (GU) toxicity was observed for grades 0, 1, 2, 3 and 4 in 73 (46%), 60 (38%), 22 (14%), 0 and 3 (2%), respectively; early gastrointestinal (GI) toxicity was recorded for grades 0, 1, 2 and 3 in 119 (75%), 37 (23%), and 2 (1%) patients, respectively.Conclusion: A combination of moderate hypofractionation, number of fractions per week adapted to target volume and precise dose delivery technique with image guidance appears safe with low early toxicity. Longer follow up is needed to assess late toxicity and tumor control probability.
Keywords: hypofractionationation; VMAT; volumetric arc therapy; RapidArc; Tumor control probability; Normal tissue complication probability; alternated time schedule